Upaya Pembinaan Masyarakat Dalam Rangka Pengembangan Susu Kambing Pasteurisasi (Suke) pada Kelompok Tani di Desa Lambanan, Kecamatan Balanipa, Kabupaten Polewali Mandar, Sulawesi Barat - Sri Gustina; Sulmiyati Sulmiyati; Magfrah Magfrah; Marsudi Marsudi (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2016)
Problems faced by the society in Lambanan village are the lack of knowledge and skills of farmers in managing the maintenance goat, the unability of utilizing and processing goat milk and most societies work as goat breeder and farmer. Purpose of this community dedication is to provide skills and the knowledge for the farmers in the Lambanan village about techniques and milking ways as well as handling and processing milk of goat. Method used is partisipative elucidation followed by demonstration and practice. Te training activities which are conducted on 25—26 June 2016 in main hall of Lambanan village ofce, began with in-class learning about maintenance management, handling, processing and marketing management the goat of PE, then followed by demonstrating outside about technique of milking and processing milk of goat pasteurization. Te products of pasteurized goat milk were packaged in glass that was commercialized with label Suke. Te conclusion of this activity shows that the training activities looked very enthusiastic to join this training and actively ask about goat milk processing.